THE INFLUENCE OF THE CASTRATION METHOD ON MEAT CUTS INDICATORS OF PIG CARCASSES - Oleksandr MYKHALKO; Mykola POVOD; Viktoriia SOKOLENKO; Serhii VERBELCHUK; Victor SHUPLYK; Nataliya SHCHERBATIUK; Volodymyr MELNYK; Liudmyla ZASUKHA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In order to determine the influence of the castration method on the indicators of the meat cuts of pig carcasses, two groups of 74 boars were selected. Surgical castration was carried out in one of them, and immunological vaccination method was used in the other group. Both surgically castrated and immunocastrated boars were reared and fattened under the same conditions. And at the end of fattening, they were slaughtered and their carcasses evaluated for weight and proportion of meat cuts separately in the cervical-scapular, back-lumbar and pelvic-femoral thirds. The result of the assessment was the establishment of a significantly higher value of the weight indicators of such meat cuts as single-grade pork from the neck by 0.3 kg or 20.0% (P <0.01) and the weight of lard with skin by 0.6 kg or 13.64 % (P <0.05) in the shoulder-scapular third of the carcass and single-grade pork per 0.2 kg or 15.38% (P <0.05) in the pelvic-femoral third of the carcass in immunocastrated pigs. A significant difference in the weight and content of other meat cuts of carcasses was not established with the use of immuno- and surgical castration of pigs.